Luminescence and Single‐Molecule‐Magnet Behaviour in Lanthanide Coordination Complexes Involving Benzothiazole‐Based Tetrathiafulvalene Ligands. Issue 3 (30th October 2017) - Kishi, Yosuke; Cornet, Louis; Pointillart, Fabrice; Riobé, François; Lefeuvre, Bertrand; Cador, Olivier; Le Guennic, Boris; Maury, Olivier; Fujiwara, Hideki; Ouahab, Lahcène
Abstract : The two ligands 4‐[6‐(1, 3‐benzothiazol‐2‐yl)pyridin‐3‐yl]‐4′, 5′‐bis(methylthio)tetrathiafulvene (L 1 ) and 4‐[6‐(1, 3‐benzothiazol‐2‐yl)pyridin‐3‐yl]‐4′, 5′‐(ethylenedithio)tetrathiafulvene (L 2 ) were developed, and six new lanthanide coordination complexes, namely, [Ln2 (hfac)6 (L 1 )2 ]· C6 H14 · x CH2 Cl2 [Ln = Dy and x = 0.25 (1 ); Ln = Yb and x = 0.30 (2 ); hfac – = 1, 1, 1, 5, 5, 5‐hexafluoroacetylacetonate], [Ln(hfac)3 (L 2 )] [Ln = Dy (3 ), Yb (4 )] and [Ln(tta)3 (L 1 )] [Ln = Yb (5 ), Er (6 ); tta – = 2‐thenoyltrifluoroacetylacetonate], were characterized by single‐crystal X‐ray diffraction. Compounds1 –6 were identified as mononuclear complexes, and the crystal packing depends on the natures of the ancillary and tetrathiafulvalene‐based ligands. The two dysprosium derivatives, 1 and3, displayed single‐molecule‐magnet behaviour in zero applied magnetic field. Although the near‐infrared luminescence of2 and4 is almost undetectable, the change of ancillary ligand switched on the Yb III (5 ) and Er III (6 ) luminescence. Abstract : The effects of the nature of the tetrathiafulvalene‐based ligand and the nature of the ancillary ligand on the luminescence and single‐molecule magnetism of mononuclear lanthanide complexes are studied.